Clinical management of metastatic kidney cancer: the role of new molecular drugs. (January 2016) - Vitale, Maria Giuseppa; Cartenì, Giacomo
Over the last few years, the most recent advances of the molecular mechanisms involved in renal cell carcinoma have led to the use of new drugs targeting VEGF, such as bevacizumab plus interferon, sorafenib, sunitinib, pazopanib, and axitinib, or the mTOR, such as temsirolimus and everolimus. The purpose of this review is to analyze the results of Phase III trial with these targeted agents, and on the management of the treatment and, in particular, when to start and to stop therapy and the use of alternative schedule of sunitinib. Recent developments in immunotherapy are also discussed.